A Comparative Study on Sideband Optimization in Time-Modulated Arrays. (29th April 2014) - Aksoy, Ertugrul; Afacan, Erkan
Abstract : A comparative analysis of the three different methods known as sideband level suppression (SBL), sideband radiation suppression (SR), and sideband bound suppression (SB) which are used in sideband calculations for time-modulated arrays (TMAs) is presented. The three methods are investigated in terms of sideband level, sideband power, time average directivity, and solution time for TMAs so as to show the performances and potentialities of these distinct techniques. The problems of interference suppression, sidelobe cancelling, and joint interference suppression and sidelobe cancelling are analyzed for a time-modulated linear array. In the linear array 30 elements are used and the interelement spacing is determined to be a half-wavelength. During the investigations, differential evolution (DE) algorithm is chosen as the optimization tool. The common variable aperture size (VAS) time schemes are optimized to synthesize the desired goals in order to compare the techniques. The results show that the SB method is more convenient than the other two compared methods.